2022
DOI: 10.1161/circgen.121.003459
|View full text |Cite
|
Sign up to set email alerts
|

How Communicating Polygenic and Clinical Risk for Atherosclerotic Cardiovascular Disease Impacts Health Behavior: an Observational Follow-up Study

Abstract: Background: Prediction tools that combine polygenic risk scores with clinical factors provide a new opportunity for improved prediction and prevention of atherosclerotic cardiovascular disease, but the clinical utility of polygenic risk score has remained unclear. Methods: We collected a prospective cohort of 7342 individuals (64% women, mean age 56 years) and estimated their 10-year risk for atherosclerotic cardiovascular disease both by a traditional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 29 publications
0
53
0
1
Order By: Relevance
“…We tested the association of the two MFGE8 variants (rs534125149 and rs201988637) with quantitative measurements of cardiometabolic relevance or known risk factors for CVD in two sub-cohorts of FinnGen, the population-based national FINRISK study 65 ( n = 26,717) and GeneRISK 66 ( n = 7239). The associations were tested across 66 quantitative measurements of cardiometabolic relevance in FINRISK, and for 158 sub-lipid species in GeneRISK.…”
Section: Methodsmentioning
confidence: 99%
“…We tested the association of the two MFGE8 variants (rs534125149 and rs201988637) with quantitative measurements of cardiometabolic relevance or known risk factors for CVD in two sub-cohorts of FinnGen, the population-based national FINRISK study 65 ( n = 26,717) and GeneRISK 66 ( n = 7239). The associations were tested across 66 quantitative measurements of cardiometabolic relevance in FINRISK, and for 158 sub-lipid species in GeneRISK.…”
Section: Methodsmentioning
confidence: 99%
“…The study included 7,292 participants, aged 45-66 years, from the ongoing prospective GeneRISK cohort recruited during 2015–2017 from Southern Finland. The recruitment process and sample collection procedures are described in detail in [42]. Briefly, participants were instructed to fast overnight for 10 hours before the blood samples were collected for plasma, serum and DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…88,98 In a single-arm study, disclosure of a higher CAD PRS may influence favorable lifestyle behaviors. 99 Beyond lifestyle changes, it appears that PRS risk correlates with medication efficacy. Subgroup analyses in primary prevention statin trials indicated that those with high CAD PRS versus others derived greater relative and absolute clinical benefit from statins versus placebo (46% versus 26%; P heterogeneity =0.05) without differences in LDL-C reduction.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%